Lithium iron phosphate positive electrode material and preparation method thereof, positive electrode plate and secondary battery
By introducing the grading of large and small particles into the lithium iron phosphate positive electrode material and regulating the morphology of the second particle, the problem of difficulty in obtaining high compaction density and excellent discharge performance in traditional methods is solved, and the efficient improvement of the material is achieved.
Patent Information
- Application Number
- CN202510031535.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-15
AI Technical Summary
It is difficult to obtain lithium iron phosphate positive electrode materials that have high compaction density and excellent discharge performance in traditional methods.
By introducing the first and second particles into the lithium iron phosphate positive electrode material, the first particles have a small particle size and a high number proportion, the second particles have a large particle size and a low number proportion, and the morphology of the second particles is regulated to make it have an elongated columnar structure.
The high compaction density and excellent discharge performance of lithium iron phosphate positive electrode material are achieved, and the sharp reduction of electrical properties is avoided.
Smart Images

Figure CN119822349A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a lithium iron phosphate positive electrode material and a preparation method thereof, a positive electrode sheet and a secondary battery. Background Art
[0002] The large-scale use of traditional fossil fuels has led to increasingly serious problems such as resource shortages and environmental pollution. It is of great significance to accelerate the transformation of energy structure and develop clean renewable energy. Among them, lithium-ion batteries are widely used in 3C products, energy storage systems and power batteries due to their high energy density, long cycle life, good rate performance and low cost. How to further improve the energy density and cycle life of lithium-ion batteries has also become a research hotspot in the field of lithium-ion batteries. As the core part of lithium-ion batteries, positive electrode materials play a vital role in the preparation of high-performance lithium-ion batteries.
[0003] Lithium iron phosphate (LiFePO4, LFP) is an important cathode material with the advantages of high safety, long cycle life, relatively low cost and good thermal stability. When lithium iron phosphate cathode materials are applied to lithium-ion batteries, their energy density is not only related to capacity, but also closely related to compaction density. There are reports that the compaction density can be increased by increasing the primary particle size, but this will lead to an increase in the overall particle size and a significant decrease in electrical performance, making it difficult to obtain lithium iron phosphate cathode materials with both high compaction density and excellent discharge performance. Summary of the invention
[0004] In view of the technical problems existing in the background technology, the present application provides a lithium iron phosphate positive electrode material and its preparation method, a positive electrode plate and a secondary battery, aiming to solve the technical problem that it is difficult to obtain a lithium iron phosphate positive electrode material with both high compaction density and excellent discharge performance in traditional methods.
[0005] In a first aspect, an embodiment of the present application provides a lithium iron phosphate positive electrode material, wherein the average particle size of primary particles of the lithium iron phosphate positive electrode material is 250nm to 330nm;
[0006] The lithium iron phosphate positive electrode material includes a first particle and a second particle;
[0007] The first particles meet the following requirements: particle size ≤ 200nm, and the number accounts for 35% to 45%;
[0008] The second particles meet the following requirements: particle size ≥ 1 μm, and the number accounts for 1% to 5%;
[0009] The second particle has a columnar structure, and the ratio of the length to the width of the columnar structure is (1.7-6):1.
[0010] In the technical solution of the embodiment of the present application, the lithium iron phosphate positive electrode material includes a first particle and a second particle, the first particle has a small particle size and a high number, and the second particle has a large particle size and a low number, wherein the first particle and the second particle form a large and small particle gradation, thereby ensuring a high compaction density of the lithium iron phosphate positive electrode material. At the same time, the second particle has a low number, and the ratio of its length to width is (1.7 to 6): 1, presenting a slender columnar structure, which can effectively inhibit the polarization of large single crystal particles, while improving the compaction density and avoiding a sharp decrease in electrical performance, thereby obtaining a lithium iron phosphate positive electrode material with high compaction density and excellent discharge performance.
[0011] In some embodiments, the expression of the lithium iron phosphate positive electrode material is LiFe 1-x M x PO4 / C;
[0012] Among them, 0 <x≤0.1;
[0013] The M element includes one or more of Mg, Ti, Mn, V, La, and Ce.
[0014] In this embodiment, after the lithium iron phosphate positive electrode material is doped with metal elements and carbon coated, the electronic conductivity is improved, the crystal structure is optimized, and the ion diffusion rate is also improved, thereby effectively achieving the improvement of the compaction density and electrical performance of the lithium iron phosphate positive electrode material.
[0015] In some embodiments, the mass fraction of carbon in the lithium iron phosphate positive electrode material is 1.20% to 1.28%.
[0016] In this embodiment, by controlling the carbon content within the above range, it is beneficial to improve the electrochemical performance of the lithium iron phosphate positive electrode material.
[0017] In some embodiments, the compaction density of the lithium iron phosphate positive electrode material is 2.53 g / cm 3 ~2.66g / cm 3 .
[0018] In this embodiment, the compaction density of the lithium iron phosphate positive electrode material is high, and particles of different sizes are well compacted, which can improve the electronic conductivity of the lithium iron phosphate material and is beneficial to improving the electrochemical performance of the battery.
[0019] In a second aspect, an embodiment of the present application provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:
[0020] preparing a precursor slurry containing anhydrous iron phosphate, a lithium source, a carbon source, a dopant, an anionic polymer and water;
[0021] The precursor slurry is dispersed, dried and sintered to obtain a lithium iron phosphate positive electrode material;
[0022] Among them, the span of the iron-phosphorus ratio of anhydrous ferric phosphate is ≥0.025, and the average iron-phosphorus ratio is 0.978-0.985;
[0023] The average particle size of the primary particles of anhydrous ferric phosphate is 270 nm to 330 nm.
[0024] In the technical solution of the embodiment of the present application, the span of the iron-phosphorus ratio of anhydrous iron phosphate is large and the average iron-phosphorus ratio is high, which means that the anhydrous iron phosphate contains a large amount of anhydrous iron phosphate with a high iron-phosphorus ratio and a small amount of anhydrous iron phosphate with a low iron-phosphorus ratio. Among them, the higher the iron-phosphorus ratio of anhydrous iron phosphate, the more difficult it is to form large-particle lithium iron phosphate grains during the sintering process. Therefore, a large amount of anhydrous iron phosphate with a high iron-phosphorus ratio can be used to form lithium iron phosphate grains with a relatively large number and a small particle size, and a small amount of anhydrous iron phosphate with a low iron-phosphorus ratio can be used to form lithium iron phosphate grains with a relatively small number and a large particle size. At the same time, the average particle size of the primary particles of anhydrous iron phosphate is moderate, which can avoid the problem of too small particle size generating a large number of lithium iron phosphate grains with too small particle size and resulting in a low compaction density, and can also reduce the grinding difficulty when grinding is used for dispersion treatment, and avoid the problem of too high iron-phosphorus ratio causing great grinding difficulty. In addition, in order to overcome the negative impact of the polarization of large single crystal particles on the discharge performance of lithium iron phosphate positive electrode materials, the embodiments of the present application utilize the complexation of anionic polymers to inhibit the growth of certain crystal planes, thereby playing a good role in crystal form regulation, ensuring that the crystal crystallization process has a certain crystal plane orientation, and prompting large single crystal particles to present a columnar structure with a high aspect ratio, effectively inhibiting the polarization of large single crystal particles, while increasing the compaction density and avoiding a sharp decrease in electrical properties, thereby obtaining a lithium iron phosphate positive electrode material with high compaction density and excellent electrical properties.
[0025] In some embodiments, the method for preparing anhydrous ferric phosphate comprises the following steps:
[0026] Mixing a ferrous solution, a phosphorus source solution, an oxidant solution and an organic base solution to obtain a first slurry;
[0027] The first slurry is filtered, rinsed and pulped, and then the pH value is adjusted and the slurry is aged to obtain a second slurry;
[0028] The second slurry is filtered, flashed and calcined to obtain anhydrous iron phosphate.
[0029] In this embodiment, the organic base can play the following roles: first, it adjusts the pH value of the reaction system, and while regulating the iron-phosphorus ratio, it can consume hydrogen ions and promote the reaction to generate iron phosphate with a high iron-phosphorus ratio; second, it has a complexing and dispersing effect similar to that of a surfactant, which can significantly reduce the surface tension of the reaction system, thereby regulating the particle size of the primary particles of iron phosphate; third, it complexes the excess metal cations, improves the efficiency of a single rinse, and accelerates the removal of impurity elements, thereby improving the purity of anhydrous iron phosphate. Therefore, by adding an organic base in the process of preparing anhydrous iron phosphate by precipitation, anhydrous iron phosphate with a moderate average particle size of primary particles, a large iron-phosphorus ratio span, a high average iron-phosphorus ratio, and high purity can be obtained, and the lithium iron phosphate positive electrode material prepared from the anhydrous iron phosphate as a precursor also has the advantages of high compaction density and excellent discharge performance.
[0030] In some embodiments, the molar ratio of ferrous ions in the ferrous solution, phosphate ions in the phosphorus source solution, the oxidant in the oxidant solution, and the organic base in the organic base solution is 1:(1.2-1.3):(2.3-2.8):(0.008-0.013).
[0031] In this embodiment, in the reaction process of preparing ferric phosphate by precipitation method, the concentration of trivalent iron and phosphate and the reaction conditions jointly determine the iron-phosphorus ratio and particle size of ferric phosphate. In this embodiment, the molar ratio of each raw material satisfies the above range, and the dual role of adjusting pH value and complexing dispersion of organic base can be fully exerted, and ferric phosphate with moderate average particle size of primary particles, large span of iron-phosphorus ratio, high average iron-phosphorus ratio and low impurity content can be obtained at an appropriate concentration.
[0032] In some embodiments, the concentration of ferrous ions in the ferrous solution is 1.5 mol / L to 2 mol / L.
[0033] In some embodiments, the pH value of the ferrous solution is 2.5-3.0.
[0034] In some embodiments, the concentration of phosphate ions in the phosphorus source solution is 1 mol / L to 2 mol / L.
[0035] In some embodiments, the pH value of the phosphorus source solution is 6.8-7.2.
[0036] In some embodiments, the oxidant in the oxidant solution includes one or more of hydrogen peroxide, ammonium persulfate, sodium persulfate, and sodium hypophosphite.
[0037] In some embodiments, the concentration of the oxidant in the oxidant solution is 7.2 mol / L to 7.7 mol / L.
[0038] In some embodiments, the organic base in the organic base solution includes one or more of triethanolamine and diethanol monoisopropanolamine.
[0039] In some embodiments, the concentration of the organic base in the organic base solution is 0.010 mol / L to 0.015 mol / L.
[0040] In this embodiment, by regulating the concentration, pH and raw materials of the ferrous solution, phosphorus source solution, oxidant solution and organic base solution, the ferric phosphate precipitation reaction process can be controlled to enable the organic base to fully exert its role in regulating acidity and alkalinity and complexing and dispersing, thereby forming anhydrous ferric phosphate with a moderate average particle size of primary particles, a large iron-phosphorus ratio span and a high average iron-phosphorus ratio.
[0041] In some embodiments, the step of mixing the ferrous solution, the phosphorus source solution, the oxidant solution and the organic base solution to obtain a first slurry comprises:
[0042] The phosphorus source solution includes a first phosphorus source solution and a second phosphorus source solution, and the oxidant solution includes a first oxidant solution and a second oxidant solution;
[0043] Mixing the ferrous solution, the first phosphorus source solution and the first oxidant solution to obtain a first mixed solution;
[0044] Mixing the first mixed solution and the organic base solution to obtain a second mixed solution;
[0045] The second phosphorus source solution and the second oxidant solution are sequentially added to the second mixed solution to obtain a first slurry.
[0046] In this embodiment, the phosphorus source solution and the oxidant solution are added in batches, which can reduce the oxidant concentration in the reaction system, ensure that the average particle size of the primary particles of iron phosphate is moderate and the iron-phosphorus ratio spans a large range, thereby ensuring that during the high-temperature sintering process, the particles with a low iron-phosphorus ratio slowly grow into large single crystal particles, and the particles with a high iron-phosphorus ratio remain in a small particle state, thereby achieving the effect of increasing the compaction density of the material.
[0047] In some embodiments, the mass ratio of the first phosphorus source solution to the second phosphorus source solution is (65-80):(20-35).
[0048] In some embodiments, the mass ratio of the first oxidant solution to the second oxidant solution is (70-85):(15-30).
[0049] In some embodiments, the step of mixing a ferrous solution, a first phosphorus source solution and a first oxidant solution to obtain a first mixed solution includes: taking the ferrous solution as the base liquid, and simultaneously adding the first phosphorus source solution and the first oxidant solution to the base liquid, the adding time is 20 minutes to 30 minutes, to obtain the first mixed solution.
[0050] In some embodiments, the step of mixing the first mixed solution and the organic base solution to obtain the second mixed solution includes: adding the organic base solution to the first mixed solution and stirring for 20 min to 40 min to obtain the second mixed solution.
[0051] In some embodiments, the step of sequentially adding a second phosphorus source solution and a second oxidant solution to a second mixed liquid to obtain a first slurry comprises: adding the second phosphorus source solution to the second mixed liquid, stirring for 2 to 10 minutes, and dripping the second oxidant solution for 30 to 50 minutes, and then stirring at 50°C to 60°C for 40 to 80 minutes to obtain the first slurry.
[0052] In some embodiments, the step of adjusting the pH value and subjecting the slurry to aging treatment to obtain the second slurry comprises: adjusting the pH value to 1.0-1.7 using phosphoric acid, and heating the mixture to 90° C.-95° C. for aging reaction until the pH value of the second slurry is 1.75-1.85.
[0053] In this embodiment, the reaction conditions and raw materials used in the step of mixing the ferrous solution, the phosphorus source solution, the oxidant solution and the organic base solution to obtain the first slurry are controlled. When the reaction conditions and the raw materials used meet the above requirements, the prepared iron phosphate has a low impurity content, a small particle size, and a large iron-phosphorus ratio span, which is conducive to the subsequent preparation of lithium iron phosphate positive electrode materials with high compaction density and good discharge performance.
[0054] In some embodiments, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium sulfate, lithium nitrate, lithium phosphate, and lithium chloride.
[0055] In some embodiments, the dopant includes one or more of magnesium oxide, titanium dioxide, manganese dioxide, vanadium pentoxide, ammonium metavanadate, lanthanum oxide, and cerium oxide.
[0056] In some embodiments, the molar ratio of the iron element in the anhydrous ferric phosphate, the lithium element in the lithium source, and the doping element in the dopant is 1:(1.03-1.06):(0.005-0.007).
[0057] In some embodiments, the carbon source includes one or more of glucose, sucrose, fructose, ascorbic acid, polyethylene glycol, polyvinyl alcohol, and starch.
[0058] In this embodiment, the selected lithium source, carbon source and dopant are all materials with wide sources and easy to obtain, which is conducive to controlling process costs.
[0059] In some embodiments, the mass ratio of the carbon source to anhydrous ferric phosphate is (13.6-15.2):100.
[0060] In this embodiment, by controlling the content of the carbon source and anhydrous iron phosphate, the carbon source can be prompted to continue to react during the high-temperature sintering process, thereby increasing the proportion of conductive carbon. At the same time, the free lithium element can be activated, further improving the electrical properties of the lithium iron phosphate positive electrode material.
[0061] In some embodiments, the anionic polymer comprises a polycarboxylic acid.
[0062] In this embodiment, the molecular structure of the polycarboxylic acid contains a large number of carboxyl groups, which can provide strong acidity and ion exchange capacity, and at the same time has a high molecular weight, so that it has good stability and dispersibility in the solution, and can play a good role in crystal surface regulation.
[0063] In some embodiments, the anionic polymer has a number average molecular weight of 60,000 to 150,000.
[0064] In this embodiment, the anionic polymer has a very high number average molecular weight, a high decomposition temperature, and a strong crystal surface regulation effect. It can effectively regulate the large single crystal particles to grow toward a slender columnar structure with a high aspect ratio, reduce the polarization effect of the large single crystal particles, and enable the large single crystal particles to maintain good discharge performance while being graded with small particles to increase the compaction density of the product.
[0065] In some embodiments, the mass ratio of the anionic polymer to anhydrous ferric phosphate is (1.5-2.4):100.
[0066] In some embodiments, the steps of dispersing, drying and sintering the precursor slurry to obtain a lithium iron phosphate positive electrode material include:
[0067] The precursor slurry is sand-milled and spray-dried at 200° C. to 240° C. to obtain a spray material;
[0068] Under the protection of protective gas, the spray material is heated to 792° C. to 798° C. and kept warm for 8 h to 11 h to obtain a lithium iron phosphate positive electrode material.
[0069] In this embodiment, by controlling the temperature of spray drying, it is possible to avoid partial decomposition of the carbon source and thus affect the carbon content of the product. By controlling the temperature and time of the sintering treatment, it is possible to avoid excessive reduction, thereby ensuring that the lithium iron phosphate positive electrode material has excellent electrical properties.
[0070] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising the lithium iron phosphate positive electrode material described in the first aspect of the present application, or comprising the lithium iron phosphate positive electrode material prepared by the preparation method of the lithium iron phosphate positive electrode material described in the second aspect of the present application.
[0071] In this embodiment, the positive electrode plate includes the above-mentioned lithium iron phosphate positive electrode material, and thus has the advantage of good electrochemical performance.
[0072] In a fourth aspect, an embodiment of the present application provides a secondary battery, comprising the positive electrode sheet shown in the third aspect of the present application.
[0073] In this embodiment, the secondary battery includes the above-mentioned positive electrode plate, and thus has excellent electrochemical performance.
[0074] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0075] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0076] Figure 1 It is a schematic diagram of a process for preparing a lithium iron phosphate positive electrode material in one embodiment of the present application;
[0077] Figure 2 This is a phase analysis comparison diagram of anhydrous ferric phosphate in Example 1 of the present application and Comparative Example 1;
[0078] Figure 3 This is a morphology result diagram of anhydrous iron phosphate in Example 1 of the present application;
[0079] Figure 4 This is a morphology result diagram of anhydrous iron phosphate in comparative example 1 of the present application;
[0080] Figure 5 This is a morphology result diagram of the lithium iron phosphate positive electrode material before crushing in Example 1 of the present application;
[0081] Figure 6 This is a diagram showing the morphology of the lithium iron phosphate positive electrode material before crushing in Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0082] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0083] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0084] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0085] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0086] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0087] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0088] In the description of the embodiments of the present application, unless otherwise specified, the solvent in the "solution" or "base solution", or "water", is at least one of distilled water, deionized water, pure water, and ultrapure water.
[0089] the term
[0090] Unless otherwise specified or there is a contradiction, the terms and phrases used in this application have the following meanings:
[0091] Particle size: For spherical particles, particle size refers to the diameter of the spherical particles. For non-spherical particles, particle size usually refers to the equivalent particle size of the non-spherical particles (generally referred to as particle size), which can be obtained by scanning electron microscope (SEM) or laser particle size analyzer testing. Among them, the equivalent particle size refers to when a physical property of a particle is the same or similar to that of a homogeneous spherical particle, the diameter of the spherical particle is used to represent the diameter of the actual particle. Unless otherwise specified or there is a contradiction, the particle size in this application represents the equivalent particle size.
[0092] Primary particle: also known as original particle or primary particle, refers to the smallest particle unit directly produced by physical or chemical methods and does not interact with each other in the initial stage of formation.
[0093] Secondary particles: larger particles formed by primary particles through agglomeration, coagulation, bonding, etc. The particle size of secondary particles is usually larger than that of primary particles, and the distribution range of particle size is wider.
[0094] Particle size distribution parameters: In the particle size distribution curve of particles, the particle size corresponding to the cumulative particle size distribution percentage reaching N% is called the DN particle size, which means that the particles smaller than this particle size account for N% of all particles, where N = 0 to 100. When N = 100, the D100 particle size indicates the particle size corresponding to the cumulative particle size distribution percentage reaching 100%. When N = 50, the D50 particle size is the particle size corresponding to the cumulative particle size distribution percentage reaching 50%, indicating the median particle size or median diameter, indicating that particles smaller than and larger than this particle size each account for 50%. For example, D50 particle size = 1mm, which means that particles with a particle size smaller than 1mm and particles with a particle size larger than 1mm each account for 50% of all particles. The DN particle size can be measured by a laser particle size analyzer.
[0095] Iron-phosphorus ratio: refers to the molar ratio of iron and phosphorus in lithium iron phosphate material, which can be expressed as Fe / P.
[0096] The span of the iron-phosphorus ratio refers to the difference between the maximum and minimum iron-phosphorus ratios in the lithium iron phosphate material. For example, if the maximum iron-phosphorus ratio of the lithium iron phosphate material is 1 and the minimum iron-phosphorus ratio is 0.98, then the span of the iron-phosphorus ratio of the lithium iron phosphate material is 0.02.
[0097] Generally speaking, the energy density of positive electrode materials applied to lithium-ion batteries is not only related to the capacity, but also closely related to the compaction density of the material. For positive electrode materials with the same capacity, the greater the compaction density, the higher the volume energy density of the battery, so compaction density is also considered to be one of the important reference indicators of material energy density. In today's era of the rise of new energy vehicles, the application scenarios of lithium iron phosphate (LFP) positive electrode materials are very broad, but their compaction density must be improved.
[0098] The improvement of the compaction density of lithium iron phosphate materials is mainly achieved through the gradation of large and small particles. The size of the primary particles can be increased by extending the insulation time, but it will cause the overall particles to become larger and the discharge performance to be significantly reduced. There are reports that disclose a method for preparing high-density lithium iron phosphate materials by pressure sintering treatment, but pressure sintering is difficult to mass produce, and the increase in the size of the primary particles will significantly reduce its discharge performance; there are reports that disclose a method for obtaining precursors of different particle sizes by sand milling treatment and preparing high-density lithium iron phosphate positive electrode materials, but this method does not describe the morphology of the precursor, and the particle size gradation of the precursor cannot change the particle size gradation of the product primary particles; there are reports that disclose a method for preparing high-density lithium iron phosphate positive electrode materials, which increases the overall particle size of the product and improves the compaction density by using anhydrous iron phosphate with different iron-phosphorus ratios and particle size control, but the high-rate performance of the lithium iron phosphate material will deteriorate, which is not conducive to its application in energy storage batteries.
[0099] It can be seen that most traditional methods improve the compaction density of lithium iron phosphate cathode materials by simultaneously increasing the primary particle size and the size particle grading. However, the presence of large single crystal particles has a great influence on the electrical properties of lithium iron phosphate cathode materials. The main reason is that the growth orientation of large single crystal particles is not obvious, and most of them are columnar structures with low aspect ratios, which makes lithium ion diffusion difficult and the discharge performance is poor. At the same time, due to the low compaction density of anhydrous iron phosphate with a high iron-phosphorus ratio, the traditional method tends to select anhydrous iron phosphate with a low iron-phosphorus ratio as a precursor. However, anhydrous iron phosphate with a low iron-phosphorus ratio is easier to grow at high temperatures, and its discharge performance is much worse than that of anhydrous iron phosphate with a high iron-phosphorus ratio. It is also impossible to produce a lithium iron phosphate cathode material with both high compaction density and excellent electrical properties.
[0100] In order to solve the technical problem that it is difficult to obtain a lithium iron phosphate positive electrode material with both high compaction density and excellent discharge performance in traditional methods, the present application provides a lithium iron phosphate material and a preparation method thereof, a positive electrode sheet and a secondary battery, wherein, by grading first particles with a small particle size and a high number proportion, and second particles with a large particle size and a low number proportion, and regulating the morphology of the second particles, a lithium iron phosphate positive electrode material with a small average particle size of primary particles, a high compaction density and excellent discharge performance is obtained, thereby improving the electrochemical performance of the positive electrode sheet and the secondary battery.
[0101] In a first aspect, an embodiment of the present application provides a lithium iron phosphate positive electrode material, wherein the average particle size of primary particles of the lithium iron phosphate positive electrode material is 250nm to 330nm;
[0102] The lithium iron phosphate positive electrode material includes a first particle and a second particle;
[0103] The first particles meet the following requirements: particle size ≤ 200nm, and the number accounts for 35% to 45%;
[0104] The second particles meet the following requirements: particle size ≥ 1 μm, and the number accounts for 1% to 5%;
[0105] The second particle has a columnar structure, and the ratio of the length to the width of the columnar structure is (1.7-6):1.
[0106] In the technical solution of the embodiment of the present application, the lithium iron phosphate positive electrode material includes a first particle and a second particle, the first particle has a small particle size and a high number ratio, and the second particle has a large particle size and a low number ratio, which not only ensures that the average particle size of the primary particles of the lithium iron phosphate positive electrode material is small, but also forms a large and small particle gradation, thereby ensuring the high compaction density of the lithium iron phosphate positive electrode material. At the same time, the second particle not only has a low number ratio, but also has a length-to-width ratio of (1.7-6):1, presenting a slender columnar structure, effectively suppressing the polarization of large single crystal particles, while improving the compaction density and avoiding a sharp decrease in electrochemical performance, thereby obtaining a lithium iron phosphate positive electrode material with high compaction density and excellent discharge performance.
[0107] As an example, the average particle size of the primary particles of the lithium iron phosphate positive electrode material includes but is not limited to 250nm, 260nm, 270nm, 280nm, 290nm, 300nm, 310nm, 320nm or 330nm. Preferably, the average particle size of the primary particles of the lithium iron phosphate positive electrode material is 270nm to 300nm.
[0108] As an example, the particle size of the first particles includes but is not limited to 20nm, 50nm, 80nm, 100nm, 120nm, 150nm, 180nm or 200nm, and the number of the first particles accounts for but is not limited to 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44% or 45%. Preferably, the number of the first particles accounts for 38% to 42%.
[0109] As an example, the particle size of the second particles includes but is not limited to 1 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2 μm, 2.2 μm, 2.5 μm, 2.8 μm, 3 μm, 4 μm, 5 μm or 10 μm, and the number of the second particles accounts for but is not limited to 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%. Preferably, the number of the second particles accounts for 2% to 3.3%.
[0110] In some embodiments, the ratio of the number of first particles to the number of second particles is (8-43):1, including but not limited to 8:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1 or 43:1. Preferably, the ratio of the number of first particles to the number of second particles is (12-20):1.
[0111] As an example, the ratio of the length to the width of the second particle includes, but is not limited to, 1.7:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1 or 6:1. Preferably, the ratio of the length to the width of the second particle is (2.8-3.5):1.
[0112] In some embodiments, the length of the second particle is 2 μm to 9 μm, and the width of the second particle is 0.3 μm to 4.1 μm. As an example, the length of the second particle includes but is not limited to 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm or 9 μm, and the width of the second particle includes but is not limited to 0.3 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm or 4.1 μm. Preferably, the length of the second particle is 4 μm to 5.1 μm, and the width of the second particle is 1.3 μm to 1.5 μm.
[0113] In some embodiments, the expression of the lithium iron phosphate positive electrode material is LiFe 1-x M x PO4 / C;
[0114] Among them, 0 <x≤0.1;
[0115] The M element includes one or more of Mg, Ti, Mn, V, La, and Ce.
[0116] Understandably, LiFe 1-x M x PO4 / C means that the lithium iron phosphate positive electrode material includes a core and a carbon layer covering the core. The core is expressed as LiFe 1-x M xPO4, x represents the stoichiometric number or doping amount of the M element. As an example, the value of x includes but is not limited to 0.001, 0.005, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09 or 0.1. The M element can be selected from any one of Mg, Ti, Mn, V, La and Ce, or at least two of the above elements, such as Mg and Ti, Mg and Mn, Mg and V, Mg and La, Mg and Ce, Ti and Mn, Ti and V, Ti and La, Ti and Ce, Mn and V, Mn and La, Mn and Ce, V and La, V and Ce, La and Ce, or a combination of Mg, Ti and Mn, etc.
[0117] In this embodiment, after the lithium iron phosphate positive electrode material is doped with metal elements and carbon coated, the electronic conductivity is improved, the crystal structure is optimized, and the ion diffusion rate is also improved, thereby effectively achieving the improvement of the compaction density and electrochemical performance of the lithium iron phosphate positive electrode material.
[0118] In some embodiments, the mass fraction of carbon in the lithium iron phosphate positive electrode material is 1.20% to 1.28%. As an example, the mass fraction of carbon in the lithium iron phosphate positive electrode material includes but is not limited to 1.20%, 1.21%, 1.22%, 1.23%, 1.24%, 1.25%, 1.26%, 1.27% or 1.28%.
[0119] In this embodiment, the lithium iron phosphate positive electrode material contains an appropriate amount of carbon element, which can enhance the overall electronic conductivity of the material, help improve the charge and discharge efficiency and rate performance of the material, and at the same time, the carbon layer coating can prevent the growth and agglomeration of particles, reduce the particle size and increase the specific surface area, which is beneficial to the deintercalation and extraction of lithium ions and the improvement of compaction density, thereby improving the energy density of the material.
[0120] In some embodiments, the compaction density of the lithium iron phosphate positive electrode material is 2.53 g / cm 3 ~2.66g / cm 3 As an example, the compaction density of lithium iron phosphate positive electrode materials includes but is not limited to 2.53 g / cm 3 , 2.54g / cm 3 , 2.55g / cm 3 , 2.56g / cm 3 , 2.57g / cm 3 , 2.58g / cm 3 , 2.59g / cm 3 , 2.60g / cm 3 , 2.61g / cm 3 , 2.62g / cm 3, 2.63g / cm 3 or 2.64 g / cm 3 Preferably, the compaction density of the lithium iron phosphate positive electrode material is 2.60 g / cm 3 ~2.66g / cm 3 .
[0121] In this embodiment, the compaction density of the lithium iron phosphate positive electrode material is high, and particles of different sizes are well compacted, which can improve the electronic conductivity of the lithium iron phosphate material and is beneficial to improving the electrochemical performance of the battery.
[0122] Please refer to Figure 1 In a second aspect, the present application provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:
[0123] S100, preparing a precursor slurry containing anhydrous iron phosphate, a lithium source, a carbon source, a dopant, an anionic polymer and water;
[0124] S200, dispersing, drying and sintering the precursor slurry to obtain a lithium iron phosphate positive electrode material;
[0125] Among them, the span of the iron-phosphorus ratio of anhydrous ferric phosphate is ≥0.025, and the average iron-phosphorus ratio is 0.978-0.985;
[0126] The average particle size of the primary particles of anhydrous ferric phosphate is 270 nm to 330 nm.
[0127] In the technical solution of the embodiment of the present application, the span of the iron-phosphorus ratio of anhydrous iron phosphate is large and the average iron-phosphorus ratio is high, which means that the anhydrous iron phosphate contains a large amount of anhydrous iron phosphate with a high iron-phosphorus ratio and a small amount of anhydrous iron phosphate with a low iron-phosphorus ratio. The higher the iron-phosphorus ratio of anhydrous iron phosphate, the more difficult it is to form large-particle lithium iron phosphate grains during the sintering process. Therefore, a large amount of anhydrous iron phosphate with a high iron-phosphorus ratio can be used to form lithium iron phosphate grains with a relatively large number and a small particle size, and a small amount of anhydrous iron phosphate with a low iron-phosphorus ratio can be used to form lithium iron phosphate grains with a relatively small number and a large particle size. At the same time, the average particle size of the primary particles of anhydrous iron phosphate is moderate, which can avoid the problem of too small particle size generating a large number of lithium iron phosphate grains with too small particle size and resulting in low compaction density, and can also reduce the difficulty of grinding and avoid the problem of too high iron-phosphorus ratio causing great difficulty in grinding. In addition, in order to overcome the negative impact of the polarization of large single crystal particles on the discharge performance of lithium iron phosphate positive electrode materials, the embodiments of the present application utilize the complexation of anionic polymers to inhibit the growth of certain crystal planes, thereby playing a good role in crystal form regulation, ensuring that the crystal crystallization process has a certain crystal plane orientation, and prompting large single crystal particles to present a columnar structure with a high aspect ratio, effectively inhibiting the polarization of large single crystal particles, while improving the compaction density. Avoid a sharp decrease in electrochemical performance, and thereby obtain a lithium iron phosphate positive electrode material with high compaction density and excellent electrochemical performance.
[0128] As an example, the span of the iron-to-phosphorus ratio of anhydrous ferric phosphate includes, but is not limited to, 0.025, 0.026, 0.027, 0.028, 0.029, 0.030, 0.031, 0.032, 0.033, 0.034 or 0.035. Preferably, the span of the iron-to-phosphorus ratio of anhydrous ferric phosphate is 0.028-0.032.
[0129] As an example, the average iron-to-phosphorus ratio of anhydrous ferric phosphate includes, but is not limited to, 0.978, 0.979, 0.980, 0.981, 0.982, 0.983, 0.984 or 0.985. Preferably, the average iron-to-phosphorus ratio of anhydrous ferric phosphate is 0.980-0.985.
[0130] As an example, the average particle size of the primary particles of anhydrous ferric phosphate includes, but is not limited to, 270 nm, 280 nm, 290 nm, 300 nm, 310 nm, 320 nm or 330 nm. Further, the average particle size of the primary particles of anhydrous ferric phosphate is 300 nm to 330 nm.
[0131] In some embodiments, the method for preparing anhydrous ferric phosphate comprises the following steps:
[0132] S110, mixing the ferrous solution, the phosphorus source solution, the oxidant solution and the organic base solution to obtain a first slurry;
[0133] S120, filtering, rinsing and beating the first slurry, and then adjusting the pH value and performing aging treatment to obtain a second slurry;
[0134] S130, filtering, flashing and calcining the second slurry to obtain anhydrous iron phosphate.
[0135] In this embodiment, the organic base can play the following roles: first, it adjusts the pH value of the reaction system, and while regulating the iron-phosphorus ratio, it can consume hydrogen ions and promote the reaction to generate iron phosphate; second, it has a complexing and dispersing effect similar to that of a surfactant, which can significantly reduce the surface tension of the reaction system, thereby regulating the particle size of the primary particles of iron phosphate; third, it complexes the excess metal cations, improves the efficiency of a single rinse, and accelerates the removal of impurity elements, thereby improving the purity of anhydrous iron phosphate. Therefore, by adding an organic base in the process of preparing anhydrous iron phosphate by precipitation, anhydrous iron phosphate with a moderate average particle size of primary particles, a large iron-phosphorus ratio span, a high average iron-phosphorus ratio, and high purity can be obtained, and the lithium iron phosphate positive electrode material prepared from the anhydrous iron phosphate as a precursor also has the advantages of high compaction density and excellent discharge performance.
[0136] In some embodiments, the molar ratio of ferrous ions in the ferrous solution, phosphate ions in the phosphorus source solution, the oxidant in the oxidant solution, and the organic base in the organic base solution is 1:(1.2-1.3):(2.3-2.8):(0.008-0.013).
[0137] As an example, the molar ratio of the ferrous ions in the ferrous solution to the phosphate ions in the phosphorus source solution includes, but is not limited to, 1:1.2, 1:1.21, 1:1.22, 1:1.23, 1:1.24, 1:1.25, 1:1.26, 1:1.27, 1:1.28, 1:1.29, or 1:1.3. The molar ratio of the ferrous ions in the ferrous solution to the oxidant in the oxidant solution includes, but is not limited to, 1:2.3, 1:2.35, 1:2.4, 1:2.45, 1:2.5, 1:2.55, 1:2.6, 1:2.65, 1:2.7, 1:2.75, or 1:2.8. The molar ratio of the ferrous ions in the ferrous solution to the organic base in the organic base solution includes, but is not limited to, 1:0.008, 1:0.009, 1:0.010, 1:0.011, 1:0.012 or 1:0.013.
[0138] In this embodiment, in the reaction process of preparing ferric phosphate by precipitation method, the concentration of trivalent iron and phosphate and the reaction conditions jointly determine the iron-phosphorus ratio and particle size of ferric phosphate. In this embodiment, the molar ratio of each raw material satisfies the above range, and the dual role of adjusting pH value and complexing dispersion of organic base can be fully exerted, and ferric phosphate with moderate average particle size of primary particles, large span of iron-phosphorus ratio, high average iron-phosphorus ratio and low impurity content can be obtained at an appropriate concentration.
[0139] In some embodiments, the concentration of ferrous ions in the ferrous solution is 1.5 mol / L to 2 mol / L. As an example, the concentration of ferrous ions in the ferrous solution includes but is not limited to 1.5 mol / L, 1.55 mol / L, 1.6 mol / L, 1.65 mol / L, 1.7 mol / L, 1.75 mol / L, 1.8 mol / L, 1.85 mol / L, 1.9 mol / L, 1.95 mol / L or 2 mol / L.
[0140] In some embodiments, the pH value of the ferrous solution is 2.5 to 3.0. As an example, the pH value of the ferrous solution includes, but is not limited to, 2.5, 2.55, 2.6, 2.65, 2.7, 2.75, 2.8, 2.85, 2.9, 2.95 or 3.0.
[0141] In certain embodiments, the ferrous ion source in the ferrous solution includes one or more of ferrous sulfate, ferrous chloride, ferrous nitrate, ferrous acetate and ferrous oxalate. It is understandable that the ferrous ion source in the ferrous solution can be selected from any one of ferrous sulfate, ferrous chloride, ferrous nitrate, ferrous acetate and ferrous oxalate, or at least two of the above-mentioned ferrous ion sources, such as ferrous sulfate and ferrous chloride, ferrous sulfate and ferrous nitrate, ferrous sulfate and ferrous acetate, ferrous sulfate and ferrous oxalate, ferrous chloride and ferrous nitrate, ferrous chloride and ferrous acetate, ferrous chloride and ferrous oxalate, ferrous nitrate and ferrous acetate, ferrous nitrate and ferrous oxalate, ferrous acetate and ferrous oxalate, and a combination of ferrous sulfate, ferrous chloride and ferrous nitrate, etc.
[0142] In some embodiments, the preparation method of ferrous solution includes the following steps: mixing titanium dioxide byproduct and water, heating to dissolve at 50°C to 80°C, then adding 5% to 15% by mass alkali solution for sedimentation, and filtering to remove impurities to obtain ferrous solution.
[0143] In this embodiment, the titanium dioxide byproduct refers to the byproduct produced by the sulfuric acid method for preparing titanium dioxide, and the main component is ferrous sulfate heptahydrate (FeSO4·7H2O). Using the titanium dioxide byproduct as a raw material can not only produce a ferrous solution with a suitable concentration and a suitable pH value, but also achieve resource recycling, reduce production costs, and have high environmental benefits.
[0144] In some embodiments, the concentration of phosphate ions in the phosphorus source solution is 1 mol / L to 2 mol / L. As an example, the concentration of phosphate ions in the phosphorus source solution includes, but is not limited to, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L or 2 mol / L.
[0145] In some embodiments, the pH value of the phosphorus source solution is 6.8 to 7.2. As an example, the pH value of the phosphorus source solution includes but is not limited to 6.8, 6.85, 6.9, 6.95, 7.0, 7.05, 7.1, 7.15 or 7.2.
[0146] In some embodiments, the preparation method of the phosphorus source solution comprises the following steps: dissolving the phosphorus source in water, filtering, adding ammonia water to adjust the pH value to 6.8-7.2, and obtaining a phosphorus source solution. The phosphorus source comprises one or more of phosphoric acid, ammonium dihydrogen phosphate, ammonium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, and sodium phosphate. It can be understood that the phosphorus source in the phosphorus source solution can be selected from any one of the above-mentioned phosphoric acid, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, and sodium phosphate, and can also be selected from a combination of at least two of the above-mentioned phosphorus sources, such as a combination of phosphoric acid, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, and ammonium phosphate.
[0147] In some embodiments, the oxidant in the oxidant solution includes one or more of hydrogen peroxide, ammonium persulfate, sodium persulfate, and sodium hypophosphite. As an example, the oxidant in the oxidant solution can be selected from any one of hydrogen peroxide, ammonium persulfate, sodium persulfate, and sodium hypophosphite, or at least two of the above oxidants can be selected, such as hydrogen peroxide and ammonium persulfate, hydrogen peroxide and sodium persulfate, hydrogen peroxide and sodium hypophosphite, ammonium persulfate and sodium persulfate, ammonium persulfate and sodium hypophosphite, sodium persulfate and sodium hypophosphite, and a combination of hydrogen peroxide, ammonium persulfate, and sodium persulfate.
[0148] In some embodiments, the concentration of the oxidant in the oxidant solution is 7.2 mol / L to 7.7 mol / L. By way of example, the concentration of the oxidant in the oxidant solution includes, but is not limited to, 7.2 mol / L, 7.25 mol / L, 7.3 mol / L, 7.35 mol / L, 7.4 mol / L, 7.45 mol / L, 7.5 mol / L, 7.55 mol / L, 7.6 mol / L, 7.65 mol / L, or 7.7 mol / L.
[0149] In certain embodiments, the organic base in the organic base solution comprises one or more of triethanolamine, diethanol monoisopropanolamine and diethanol monoisopropanolamine. It is understandable that the organic base in the organic base solution can be selected from any one of triethanolamine, diethanol monoisopropanolamine and diethanol monoisopropanolamine, or can be selected from at least two of the above-mentioned organic bases, such as triethanolamine and diethanol monoisopropanolamine, triethanolamine and diethanol monoisopropanolamine, diethanol monoisopropanolamine and diethanol monoisopropanolamine, and a combination of triethanolamine, diethanol monoisopropanolamine and diethanol monoisopropanolamine.
[0150] In some embodiments, the organic base in the organic base solution is further preferably at least two of triethanolamine, diethanol monoisopropanolamine and diethanol monoisopropanolamine.
[0151] In this embodiment, at least two organic bases are selected for compounding, and their complexing and dispersing effect is significantly better than that of a single organic base, and the effect of regulating the particle size and iron-phosphorus ratio of iron phosphate is better, which is beneficial to improving the compaction density and discharge performance of lithium iron phosphate.
[0152] In some embodiments, the concentration of the organic base in the organic base solution is 0.010 mol / L to 0.015 mol / L. As an example, the concentration of the organic base in the organic base solution includes but is not limited to 0.010 mol / L, 0.011 mol / L, 0.012 mol / L, 0.013 mol / L, 0.014 mol / L or 0.015 mol / L.
[0153] In this embodiment, by regulating the concentration, pH and raw materials of the ferrous solution, phosphorus source solution, oxidant solution and organic base solution, the reaction conditions in the ferric phosphate precipitation process can be regulated, and the organic base can be prompted to fully exert the role of adjusting acidity and alkalinity and complexing dispersion, thereby forming anhydrous ferric phosphate with a moderate average particle size of primary particles, a large iron-phosphorus ratio span and a high average iron-phosphorus ratio.
[0154] In some embodiments, the step of mixing the ferrous solution, the phosphorus source solution, the oxidant solution and the organic base solution to obtain a first slurry comprises:
[0155] S111, the phosphorus source solution includes a first phosphorus source solution and a second phosphorus source solution, and the oxidant solution includes a first oxidant solution and a second oxidant solution;
[0156] S112, mixing the ferrous solution, the first phosphorus source solution and the first oxidant solution to obtain a first mixed solution;
[0157] S113, mixing the first mixed solution and the organic base solution to obtain a second mixed solution;
[0158] S114, sequentially adding a second phosphorus source solution and a second oxidant solution to the second mixed solution to obtain a first slurry.
[0159] In this embodiment, the phosphorus source solution and the oxidant solution are added in batches, which can reduce the oxidant concentration in the reaction system, ensure that the average particle size of the primary particles of iron phosphate is moderate and the iron-phosphorus ratio spans a large range, thereby ensuring that during the high-temperature sintering process, the particles with a low iron-phosphorus ratio slowly grow into large single crystal particles, and the particles with a high iron-phosphorus ratio remain in a small particle state, thereby achieving the effect of increasing the compaction density of the material.
[0160] In some embodiments, the mass ratio of the first phosphorus source solution to the second phosphorus source solution is (65-80):(20-35). As an example, the mass ratio of the first phosphorus source solution to the second phosphorus source solution includes but is not limited to 65:20, 65:25, 65:30, 65:35, 70:20, 70:25, 70:30, 70:35, 75:20, 75:25, 75:30, 75:35, 80:20, 80:25, 80:30 or 80:35.
[0161] In some embodiments, the mass ratio of the first oxidant solution to the second oxidant solution is (70-85):(15-30). As an example, the mass ratio of the first oxidant solution to the second oxidant solution includes but is not limited to 70:15, 70:20, 70:25, 70:30, 75:15, 75:20, 75:25, 75:30, 80:15, 80:20, 80:25, 80:30, 85:15, 85:20, 85:25 or 85:30.
[0162] In some embodiments, the step of mixing a ferrous solution, a first phosphorus source solution and a first oxidant solution to obtain a first mixed solution includes: taking the ferrous solution as the base liquid, and simultaneously adding the first phosphorus source solution and the first oxidant solution to the base liquid, the adding time is 20 minutes to 30 minutes, to obtain the first mixed solution.
[0163] As an example, the duration of adding the first phosphorus source solution and the first oxidant solution includes but is not limited to 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min or 30 min.
[0164] In some embodiments, the step of mixing the first mixed solution and the organic base solution to obtain the second mixed solution includes: adding the organic base solution to the first mixed solution at one time, and stirring for 20 minutes to 40 minutes to obtain the second mixed solution.
[0165] As an example, the stirring time after adding the organic base solution includes but is not limited to 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, 32 min, 34 min, 36 min, 38 min or 40 min.
[0166] In some embodiments, the step of sequentially adding a second phosphorus source solution and a second oxidant solution to a second mixed liquid to obtain a first slurry comprises: adding the second phosphorus source solution to the second mixed liquid at one time, stirring for 2 to 10 minutes, and dripping the second oxidant solution for 30 to 50 minutes, and then stirring at 50 to 60 degrees Celsius for 40 to 80 minutes to obtain a first slurry.
[0167] As an example, the stirring time after adding the second phosphorus source solution includes but is not limited to 2min, 3min, 4min, 5min, 6min, 7min, 8min, 9min or 10min. The dripping time of the second oxidant solution includes but is not limited to 30min, 32min, 34min, 36min, 38min, 40min, 42min, 44min, 46min, 48min or 50min. The stirring temperature after the second oxidant solution is added includes but is not limited to 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, and the stirring time includes but is not limited to 40min, 45min, 50min, 55min, 60min, 65min, 70min, 75min or 80min.
[0168] In some embodiments, the step of adjusting the pH value and subjecting the slurry to aging treatment to obtain the second slurry comprises: adjusting the pH value to 1.0-1.7 using phosphoric acid, and heating the mixture to 90° C.-95° C. for aging reaction until the pH value of the second slurry is 1.75-1.85.
[0169] As an example, the pH value after adding phosphoric acid includes but is not limited to 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6 or 1.7. The temperature of the aging reaction includes but is not limited to 90° C., 91° C., 92° C., 93° C., 94° C. or 95° C. After the aging reaction, the pH value of the second slurry includes but is not limited to 1.75, 1.76, 1.77, 1.78, 1.79, 1.80, 1.81, 1.82, 1.83, 1.84 or 1.85.
[0170] In some embodiments, the filtration process in step S120 and the filtration process in step S130 each independently include one or more of ordinary filtration, pressure filtration and suction filtration.
[0171] In some embodiments, in step S130, after filtering and flash evaporating the second slurry, calcination is performed at 750° C. to 780° C. for 3 h to 6 h to remove bound water in ferric phosphate dihydrate, thereby obtaining anhydrous ferric phosphate.
[0172] In some embodiments, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium sulfate, lithium nitrate, lithium phosphate and lithium chloride. It is understandable that the lithium source can be selected from any one of lithium carbonate, lithium hydroxide, lithium sulfate, lithium nitrate, lithium phosphate and lithium chloride, or at least two of the above lithium sources, such as lithium carbonate and lithium hydroxide, lithium carbonate and lithium sulfate, lithium carbonate and lithium nitrate, lithium carbonate and lithium phosphate, lithium carbonate and lithium chloride, lithium hydroxide and lithium sulfate, lithium hydroxide and lithium nitrate, lithium hydroxide and lithium phosphate, lithium hydroxide and lithium chloride, lithium sulfate and lithium nitrate, lithium sulfate and lithium phosphate, lithium sulfate and lithium chloride, lithium nitrate and lithium phosphate, lithium nitrate and lithium chloride, lithium phosphate and lithium chloride, and combinations of lithium carbonate, lithium hydroxide and lithium phosphate, etc.
[0173] In some embodiments, the dopant includes one or more of magnesium oxide, titanium dioxide, manganese dioxide, vanadium pentoxide, ammonium metavanadate, lanthanum oxide, and cerium oxide. It can be understood that the dopant can be selected from any one of magnesium oxide, titanium dioxide, manganese dioxide, vanadium pentoxide, ammonium metavanadate, lanthanum oxide and cerium oxide, or can be selected from at least two of the above dopants, such as magnesium oxide and titanium dioxide, magnesium oxide and manganese dioxide, magnesium oxide and vanadium pentoxide, magnesium oxide and ammonium metavanadate, magnesium oxide and lanthanum oxide, magnesium oxide and cerium oxide, titanium oxide and manganese dioxide, titanium oxide and vanadium pentoxide, titanium oxide and ammonium metavanadate, titanium oxide and lanthanum oxide, titanium oxide and cerium oxide, manganese dioxide and vanadium pentoxide, manganese dioxide and ammonium metavanadate, manganese dioxide and lanthanum oxide, manganese dioxide and cerium oxide, vanadium pentoxide and ammonium metavanadate, vanadium pentoxide and lanthanum oxide, vanadium pentoxide and cerium oxide, ammonium metavanadate and lanthanum oxide, ammonium metavanadate and cerium oxide, lanthanum oxide and cerium oxide, and a combination of magnesium oxide, titanium dioxide and manganese dioxide, etc.
[0174] In some embodiments, the molar ratio of the iron element in the anhydrous iron phosphate, the lithium element in the lithium source, and the doping element in the dopant is 1: (1.03-1.06): (0.005-0.007). As an example, the molar ratio of the iron element in the anhydrous iron phosphate to the lithium element in the lithium source includes but is not limited to 1: 1.03, 1: 1.035, 1: 1.04, 1: 1.045, 1: 1.05, 1: 1.055 or 1: 1.06; the molar ratio of the iron element in the anhydrous iron phosphate to the doping element in the dopant includes but is not limited to 1: 0.005, 1: 0.0055, 1: 0.006, 1: 0.0065 or 1: 0.007.
[0175] In certain embodiments, the carbon source comprises one or more of glucose, sucrose, fructose, ascorbic acid, polyethylene glycol, polyvinyl alcohol and starch. It is understandable that the carbon source can be selected from any one of glucose, sucrose, fructose, ascorbic acid, polyethylene glycol, polyvinyl alcohol and starch, or at least two of the above carbon sources, such as glucose and sucrose, glucose and fructose, glucose and ascorbic acid, glucose and polyethylene glycol, glucose and polyvinyl alcohol, glucose and starch, sucrose and fructose, sucrose and ascorbic acid, sucrose and polyethylene glycol, sucrose and polyvinyl alcohol, sucrose and starch, fructose and ascorbic acid, fructose and polyethylene glycol, fructose and polyvinyl alcohol, fructose and starch, ascorbic acid and polyethylene glycol, ascorbic acid and polyvinyl alcohol, ascorbic acid and starch, polyethylene glycol and polyvinyl alcohol, polyethylene glycol and starch, polyvinyl alcohol and starch, and combinations of glucose, sucrose, ascorbic acid and polyethylene glycol, etc. Among them, the molecular weight of polyethylene glycol can be 200 to 10000, including but not limited to PEG200, PEG400, PEG600, PEG1000, PEG2000, PEG4000, PEG6000, PEG8000, PEG10000 and the like.
[0176] In some embodiments, the mass ratio of the carbon source to anhydrous ferric phosphate is (13.6-15.2): 100. As an example, the mass ratio of the carbon source to anhydrous ferric phosphate includes but is not limited to 13.6:100, 13.8:100, 14.0:100, 14.2:100, 14.4:100, 14.6:100, 14.8:100 or 15.0:100.
[0177] In this embodiment, by controlling the contents of the carbon source and anhydrous iron phosphate, the carbon source can be prompted to react continuously during the high-temperature sintering process, thereby increasing the proportion of conductive carbon. At the same time, the free lithium element can be activated, further improving the electrochemical properties of the lithium iron phosphate positive electrode material.
[0178] In some embodiments, the anionic polymer comprises a polycarboxylic acid.
[0179] It can be understood that polycarboxylic acid is a type of polymer obtained by polymerization of monomers containing carboxyl groups, such as acrylic acid, maleic acid and other monomers. Polycarboxylic acid contains a large number of carboxyl groups in its molecular structure, which can provide strong acidity and ion exchange capacity, and has a high molecular weight, so that it has good stability and dispersibility in solution. It is often used as a concrete admixture (such as water reducer, slump inhibitor), detergent, scale inhibitor, dispersant, complexing agent, etc. In some specific examples, polycarboxylic acid can use Sika 504P polycarboxylic acid dispersant, or BASF RHEOPLUS 412 slump inhibitor.
[0180] In some embodiments, the number average molecular weight of the anionic polymer is 60000 to 150000. By way of example, the number average molecular weight of the anionic polymer includes, but is not limited to, 60000, 70000, 80000, 90000, 100000, 110000, 120000, 130000, 140000 or 150000.
[0181] In this embodiment, the anionic polymer has a very high number average molecular weight, a high decomposition temperature, and a strong crystal surface regulation effect. It can effectively regulate the large single crystal particles to grow toward a slender columnar structure with a high aspect ratio, reduce the polarization effect of the large single crystal particles, and enable the large single crystal particles to maintain good discharge performance while being graded with small particles to increase the compaction density of the product.
[0182] In some embodiments, the mass ratio of the anionic polymer to the anhydrous ferric phosphate is (1.5-2.4): 100. As an example, the mass ratio of the anionic polymer to the anhydrous ferric phosphate includes but is not limited to 1.5:100, 1.6:100, 1.7:100, 1.8:100, 1.9:100, 2.0:100, 2.1:100, 2.2:100, 2.3:100 or 2.4:100.
[0183] In some embodiments, the steps of dispersing, drying and sintering the precursor slurry to obtain a lithium iron phosphate positive electrode material include:
[0184] The precursor slurry is sand-milled and spray-dried at 200° C. to 240° C. to obtain a spray material;
[0185] Under the protection of protective gas, the spray material is heated to 792° C. to 798° C. and kept warm for 8 h to 11 h to obtain a lithium iron phosphate positive electrode material.
[0186] As an example, the temperature of spray drying is 200° C. to 240° C., including but not limited to 200° C., 205° C., 210° C., 215° C., 220° C., 225° C., 230° C., 235° C. or 240° C. The sintering temperature of the sintering treatment is 792° C. to 798° C., including but not limited to 792° C., 793° C., 794° C., 795° C., 796° C., 797° C. or 798° C. The holding time of the sintering treatment is 8 h to 11 h, including but not limited to 8 h, 8.5 h, 9 h, 9.5 h, 10 h, 10.5 h or 11 h.
[0187] In this embodiment, by controlling the temperature of spray drying, it is possible to avoid partial decomposition of the carbon source and thus affect the carbon content of the product. By controlling the temperature and time of the sintering treatment, it is possible to avoid excessive reduction, thereby ensuring that the lithium iron phosphate positive electrode material has excellent electrochemical properties.
[0188] In some embodiments, the precursor slurry is sand-milled to obtain a sand-milled material with a D50 particle size of 0.3 μm to 0.5 μm; and spray-dried at 200° C. to 240° C. to obtain a spray material with a D50 particle size of 20 μm to 35 μm.
[0189] As an example, the D50 particle size of the sanding material includes, but is not limited to, 0.3 μm, 0.32 μm, 0.34 μm, 0.36 μm, 0.38 μm, 0.4 μm, 0.42 μm, 0.44 μm, 0.46 μm, 0.48 μm or 0.5 μm. The D50 particle size of the spray material includes, but is not limited to, 20 μm, 22 μm, 24 μm, 26 μm, 28 μm, 30 μm, 32 μm, 34 μm or 35 μm.
[0190] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising the lithium iron phosphate positive electrode material described in the first aspect of the present application, or comprising the lithium iron phosphate positive electrode material prepared by the preparation method of the lithium iron phosphate positive electrode material described in the second aspect of the present application.
[0191] In this embodiment, the positive electrode plate includes the above-mentioned lithium iron phosphate material, and thus has excellent electrochemical properties.
[0192] In a fourth aspect, an embodiment of the present application provides a secondary battery, comprising the positive electrode sheet shown in the third aspect of the present application.
[0193] In this embodiment, the secondary battery includes the above-mentioned positive electrode plate, and thus has the advantages of high capacity and good rate performance.
[0194] In some embodiments, the 0.1C first charge specific capacity of the lithium iron phosphate positive electrode material is ≥158mAh / g, including but not limited to 158mAh / g, 159mAh / g, 160mAh / g, 161mAh / g, 162mAh / g, 163mAh / g, 164mAh / g or 165mAh / g, and is further preferably 158.5mAh / g to 162.1mAh / g.
[0195] In some embodiments, the 0.1C first discharge specific capacity of the lithium iron phosphate positive electrode material is ≥156mAh / g, including but not limited to 156mAh / g, 157mAh / g, 158mAh / g, 159mAh / g, 160mAh / g, 161mAh / g or 162mAh / g, and is further preferably 156.3mAh / g to 160.6mAh / g.
[0196] In some embodiments, the 0.1C first discharge efficiency of the lithium iron phosphate positive electrode material is ≥97%, including but not limited to 97%, 97.5%, 98%, 98.5%, 99%, 99.2%, 99.5% or 99.9%, and is further preferably 97.28% to 99.69%.
[0197] In some embodiments, the 1C first charge specific capacity of the lithium iron phosphate positive electrode material is ≥159 mAh / g, including but not limited to 159 mAh / g, 160 mAh / g, 161 mAh / g, 162 mAh / g, 163 mAh / g, 164 mAh / g or 165 mAh / g, and is further preferably 159.7 mAh / g to 161.7 mAh / g.
[0198] In some embodiments, the 1C first discharge specific capacity of the lithium iron phosphate positive electrode material is ≥158mAh / g, including but not limited to 142mAh / g, 143mAh / g, 144mAh / g, 145mAh / g, 146mAh / g, 147mAh / g, 148mAh / g, 149mAh / g or 150mAh / g, and is further preferably 142.4mAh / g to 147.2mAh / g.
[0199] In some embodiments, the 1C first discharge efficiency of the lithium iron phosphate positive electrode material is ≥88%, including but not limited to 88%, 88.5%, 89%, 89.5%, 90%, 90.5%, 91%, 91.5% or 92%, and is further preferably 88.5% to 91.43%.
[0200] In this embodiment, the lithium iron phosphate positive electrode material has high discharge specific capacity, high discharge specific capacity and good rate performance, showing excellent rapid charge and discharge capabilities, and is suitable for high power output application scenarios.
[0201] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0202] 1. Preparation method
[0203] Example 1
[0204] The preparation method of the lithium iron phosphate positive electrode material of this embodiment is as follows:
[0205] (1) Preparation of ferrous solution: Mix titanium dioxide byproduct and water, heat at 65°C to dissolve, then add 10% by mass NaOH solution for sedimentation, and filter press to remove impurities to obtain a ferrous solution with a ferrous ion concentration of 2 mol / L and a pH value of 2.5.
[0206] (2) Preparation of phosphorus source solution: Mix industrial grade diammonium phosphate, phosphoric acid and water, filter after dissolving, and add ammonia water to adjust the pH value to neutral to obtain PO4 3- A phosphorus source solution with a concentration of 2 mol / L and a pH value of 7.0.
[0207] (3) Preparation of oxidant solution: A 30% by mass H2O2 solution was diluted with pure water to obtain an oxidant solution with a H2O2 concentration of 7.35 mol / L.
[0208] (4) Preparation of organic base solution: dilute a mixture of triethanolamine and diethanol monoisopropanolamine in a mass ratio of 1:3 with water to obtain an organic base solution with an organic base concentration of 0.010 mol / L.
[0209] (5) Preparation of anhydrous ferric phosphate:
[0210] The molar ratio of ferrous ions in the ferrous solution, phosphate ions in the phosphorus source solution, the oxidant in the oxidant solution, and the organic base in the organic base solution is controlled to be 1:1.3:2.4:0.013, the phosphorus source solution is divided into a first phosphorus source solution and a second phosphorus source solution with a mass ratio of 80:20, and the oxidant solution is divided into a first oxidant solution and a second oxidant solution with a mass ratio of 85:15, and then the following treatment is performed:
[0211] A ferrous solution was added into the reaction kettle as a base liquid, and the first phosphorus source solution and the second phosphorus source solution were simultaneously dripped into the base liquid for reaction, the dripping time was 30 minutes, and a first mixed solution was obtained; an organic base solution was added into the first mixed solution at one time, and the mixture was stirred for reaction for 30 minutes to obtain a second mixed solution; a second phosphorus source solution was added into the second mixed solution at one time and stirred for 5 minutes, and then a second oxidant solution was slowly dripped therein for 30 minutes, and then the mixture was stirred for reaction at 60°C for 1 hour to obtain a first slurry.
[0212] The first slurry was filter-filtered, rinsed and beaten, and then phosphoric acid was added to adjust the pH value to 1.3, followed by heating to 95°C and aging reaction for 1 hour under rapid stirring conditions to obtain a second slurry with a pH value of 1.8; the second slurry was filter-filtered and flash-evaporated, and then calcined at 755°C for 4 hours, and crushed and sieved to obtain anhydrous iron phosphate.
[0213] (6) Preparation of lithium iron phosphate positive electrode material:
[0214] Anhydrous ferric phosphate, lithium source, dopant, carbon source, anionic polymer and pure water are mixed to obtain a precursor slurry with a solid content of 45%. Among them, the molar ratio of iron element in anhydrous ferric phosphate, lithium element in lithium source and doping element in dopant is 1:1.03:0.0055, lithium source is lithium carbonate, dopant is boron oxide and magnesium oxide with a mass ratio of 1:4; the mass ratio of carbon source and anhydrous ferric phosphate is 14.5:100, and the carbon source is glucose monohydrate; the mass ratio of anionic polymer and anhydrous ferric phosphate is 1.8:100, and the anionic polymer is BASF RHEOPLUS 412 collapse inhibitor, and the active ingredient is polycarboxylic acid with a number average molecular weight of 100,000.
[0215] The precursor slurry was sand-milled to a D50 particle size of 0.42 μm, and then spray-dried at 220°C to obtain a spray material with a D50 particle size of 24 μm; under the protection of nitrogen, the temperature was heated to 792°C at a heating rate of 5°C / min for sintering, and kept warm for 8 hours, then cooled to below 100°C by air cooling, taken out of the furnace, and crushed to obtain a lithium iron phosphate positive electrode material.
[0216] Example 2
[0217] The preparation method of the lithium iron phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:
[0218] In step (4), water is added to dilute a mixed solution in which the total mass fraction of the organic base is 85% and the mass ratio of triethanolamine to diethanol monoisopropanolamine is 1:1, to obtain an organic base solution with an organic base concentration of 0.01 mol / L.
[0219] Example 3
[0220] The preparation method of the lithium iron phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:
[0221] In step (4), water is added to dilute a mixed solution in which the total mass fraction of the organic base is 85% and the mass ratio of triethanolamine to diethanol monoisopropanolamine is 1:5, to obtain an organic base solution with an organic base concentration of 0.01 mol / L.
[0222] Example 4
[0223] The preparation method of the lithium iron phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:
[0224] In step (4), diethanol monoisopropanolamine having a mass fraction of 85% is diluted with water to obtain an organic base solution having a diethanol monoisopropanolamine concentration of 0.010 mol / L.
[0225] Example 5
[0226] The preparation method of the lithium iron phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:
[0227] In step (4), water is added to dilute a mixed solution in which the total mass fraction of the organic base is 85% and the mass ratio of triethanolamine to diethanol monoisopropanolamine is 1:3, to obtain an organic base solution with an organic base concentration of 0.013 mol / L.
[0228] Example 6
[0229] The preparation method of the lithium iron phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:
[0230] In step (4), water is added to dilute a mixed solution in which the total mass fraction of the organic base is 85% and the mass ratio of triethanolamine to diethanol monoisopropanolamine is 1:3, to obtain an organic base solution with an organic base concentration of 0.015 mol / L.
[0231] Example 7
[0232] The preparation method of the lithium iron phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:
[0233] In step (5), the molar ratio of ferrous ions in the ferrous solution, phosphate ions in the phosphorus source solution, the oxidant in the oxidant solution, and the organic base in the organic base solution is controlled to be 1:1.3:2.4:0.010.
[0234] Example 8
[0235] The preparation method of the lithium iron phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:
[0236] In step (5), the molar ratio of ferrous ions in the ferrous solution, phosphate ions in the phosphorus source solution, the oxidant in the oxidant solution and the organic base in the organic base solution is controlled to be 1:1.3:2.4:0.008.
[0237] Example 9
[0238] The preparation method of the lithium iron phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that the raw materials of the ferrous solution, the phosphorus source solution and the oxidant solution are different, as follows:
[0239] (1) Preparation of ferrous solution: Dissolve ferrous sulfate heptahydrate in water to prepare a ferrous solution with a ferrous ion concentration of 1 mol / L and a pH value of 3.7.
[0240] (2) Preparation of phosphorus source solution: Mix ammonium phosphate, phosphoric acid and water, filter after dissolving, and add ammonia water to adjust the pH value to neutral to obtain PO4 3- A phosphorus source solution with a concentration of 2 mol / L and a pH value of 7.0.
[0241] (3) Preparation of oxidant solution: Dissolve ammonium persulfate in water to obtain an oxidant solution with an ammonium persulfate concentration of 7 mol / L.
[0242] Steps (4) to (6) are the same as in Example 1.
[0243] Example 10
[0244] The preparation method of the lithium iron phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:
[0245] In step (5), the phosphorus source solution is divided into a first phosphorus source solution and a second phosphorus source solution in a mass ratio of 72:28, and the oxidant solution is divided into a first oxidant solution and a second oxidant solution in a mass ratio of 78:22.
[0246] Embodiment 11
[0247] The preparation method of the lithium iron phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:
[0248] In step (5), the phosphorus source solution is divided into a first phosphorus source solution and a second phosphorus source solution in a mass ratio of 65:35, and the oxidant solution is divided into a first oxidant solution and a second oxidant solution in a mass ratio of 70:30.
[0249] Example 12
[0250] The preparation method of the lithium iron phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:
[0251] In step (6), the molar ratio of the iron element in the anhydrous ferric phosphate, the lithium element in the lithium source and the doping element in the dopant is 1:1.045:0.0062.
[0252] Example 13
[0253] The preparation method of the lithium iron phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:
[0254] In step (6), the molar ratio of the iron element in the anhydrous ferric phosphate, the lithium element in the lithium source and the doping element in the dopant is 1:1.06:0.007.
[0255] Embodiment 14
[0256] The preparation method of the lithium iron phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:
[0257] In step (6), the mass ratio of the carbon source to anhydrous ferric phosphate is 13.6:100.
[0258] Embodiment 15
[0259] The preparation method of the lithium iron phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:
[0260] In step (6), the mass ratio of the carbon source to anhydrous ferric phosphate is 15.2:100.
[0261] Example 16
[0262] The preparation method of the lithium iron phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:
[0263] In step (6), the mass ratio of the anionic polymer to anhydrous ferric phosphate is 1.5:100.
[0264] Embodiment 17
[0265] The preparation method of the lithium iron phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:
[0266] In step (6), the mass ratio of the anionic polymer to anhydrous ferric phosphate is 2.4:100.
[0267] Embodiment 18
[0268] The preparation method of the lithium iron phosphate positive electrode material provided in this embodiment is the same or similar to that in embodiment 1, except that:
[0269] In step (6), the anionic polymer is selected from Sika 504P polycarboxylic acid dispersant, and the active ingredient is polycarboxylic acid with a number average molecular weight of 85,000.
[0270] Comparative Example 1
[0271] The preparation method of the lithium iron phosphate positive electrode material provided in this comparative example is the same or similar to that in Example 1, except that:
[0272] In step (5), no organic base solution is added to the first mixed solution, and the second phosphorus source solution is added at once and the second oxidant solution is slowly added dropwise, and reacted to obtain a first slurry;
[0273] In step (6), no anionic polymer is added to the precursor slurry.
[0274] Comparative Example 2
[0275] The preparation method of the lithium iron phosphate positive electrode material provided in this comparative example is the same or similar to that in Example 1, except that:
[0276] In step (5), no organic base solution is added to the first mixed solution, and the second phosphorus source solution is added at once and the second oxidant solution is slowly added dropwise, and reacted to obtain a first slurry;
[0277] Comparative Example 3
[0278] The preparation method of the lithium iron phosphate positive electrode material provided in this comparative example is the same or similar to that in Example 1, except that:
[0279] In step (6), no anionic polymer is added to the precursor slurry.
[0280] Comparative Example 4
[0281] The preparation method of the lithium iron phosphate positive electrode material provided in this comparative example is the same or similar to that in Example 1, except that:
[0282] In step (5), the order of feeding the phosphorus source solution, the oxidant solution and the organic base solution is different, namely:
[0283] A ferrous solution was added to the reaction kettle as a base liquid, and a phosphorus source solution, an oxidant solution and an organic base solution were simultaneously added to the base liquid, and the mixture was stirred and reacted at 60° C. for 1 hour to obtain a first slurry; then, a lithium iron phosphate positive electrode material was obtained according to steps (5) and (6) of Example 1.
[0284] 2. Test Method
[0285] 1. Property test of anhydrous iron phosphate and lithium iron phosphate materials
[0286] 1) Carbon content test: infrared carbon sulfur analyzer, model HCS-140, Shanghai Dekai Instrument Co., Ltd.
[0287] 2) Iron-phosphorus ratio test: The iron content was detected by potassium dichromate titration method, and the phosphorus content was detected by quinoline phosphomolybdic acid weight method, and the corresponding iron-phosphorus ratio was calculated;
[0288] Taking Example 1 as an example, the solid products in the first slurry and the second slurry were respectively taken for iron-phosphorus ratio test to obtain the iron-phosphorus ratio of the iron phosphate precipitated at different reaction stages, thereby obtaining the change of the iron-phosphorus ratio of the iron phosphate precipitate.
[0289] Meanwhile, after the second slurry is subjected to filter pressing, flash evaporation, calcination, pulverization and sieving, anhydrous ferric phosphate is taken for an iron-phosphorus ratio test to obtain an average iron-phosphorus ratio of the anhydrous ferric phosphate.
[0290] 3) SEM test: JSM6390 scanning electron microscope (SEM) was used for morphological characterization, and NanoMeasurer software was used to analyze the particle size and distribution of primary particles.
[0291] 4) XRD test: X-ray diffraction analysis (XRD) was used to determine the composition and content of the phases in the sample. An Empyrean rotating anode X-ray diffractometer from PANalytical of the Netherlands was used.
[0292] 5) Compaction density test: refer to GB / T 7314-2017 Metal Material Room Temperature Compression Test Method, and use an electronic compression testing machine for testing.
[0293] 6) BET specific surface area test: The specific surface area was tested using a nitrogen adsorption method.
[0294] 2. Properties test of secondary batteries
[0295] The lithium iron phosphate positive electrode material prepared in each embodiment and each comparative example is used as the positive electrode material of the lithium battery, acetylene black is used as the conductive agent, polytetrafluoroethylene is used as the binder, and the positive electrode plate is made according to the mass ratio of the positive electrode material, the conductive agent and the binder of 90:5:5, and the lithium plate is used as the negative electrode plate to assemble into a CR2032 button battery. Under the environment of 2V~3.75V, 25℃±0.5℃, 0.1C and 1C charging and discharging are tested, and under the environment of 2.5V~3.75V, 25℃±0.5℃, 1P constant power charging and discharging are tested.
[0296] III. Analysis of test results of various embodiments and comparative examples
[0297] The above test results are shown in Tables 1 to 4 and Figure 2 to Figure 6 .
[0298] Table 1. Changes in the iron-phosphorus ratio of iron phosphate during the reaction
[0299]
[0300] Table 2. Related parameters of anhydrous ferric phosphate
[0301]
[0302] Table 3. Related parameters of lithium iron phosphate cathode materials
[0303]
[0304] Note: The first particle is a lithium iron phosphate particle with a particle size of ≤200nm, and the second particle is a lithium iron phosphate particle with a particle size of ≥1μm.
[0305] Table 4. Electrical properties of lithium iron phosphate cathode materials
[0306]
[0307] (1) Changes in the iron-phosphorus ratio of iron phosphate during the reaction:
[0308] As shown in Table 1, the iron-phosphorus ratio of the first slurry obtained in Examples 1, 11 and 12 is 0.960-0.963, the iron-phosphorus ratio of the second slurry obtained is 0.988-0.994, the difference between the iron-phosphorus ratio of the second slurry and the iron-phosphorus ratio of the first slurry is 0.028-0.031, and the average iron-phosphorus ratio of the finally obtained anhydrous ferric phosphate is 0.980-0.985. It can be seen that the anhydrous ferric phosphate obtained in the above examples has a large span of phosphorus-iron ratio and a high average iron-phosphorus ratio.
[0309] No organic base solution was added to Comparative Example 1, so that the difference between the iron-phosphorus ratio of the second slurry obtained in Comparative Example 1 and the iron-phosphorus ratio of the first slurry was reduced to 0.013, and the average iron-phosphorus ratio of the obtained anhydrous iron phosphate was reduced to 0.968, which proved that the introduction of organic base can promote the reaction in the direction of generating iron phosphate, and can regulate the iron-phosphorus ratio of iron phosphate through complexation and dispersion, thereby improving the iron-phosphorus ratio span and average iron-phosphorus ratio of anhydrous iron phosphate.
[0310] In Comparative Example 4, the phosphorus source solution, the oxidant solution and the organic alkali solution are added to the ferrous solution at one time, so that the difference between the iron-phosphorus ratio of the second slurry obtained in Comparative Example 4 and the iron-phosphorus ratio of the first slurry is reduced to 0.014, and the iron-phosphorus ratio of the obtained anhydrous ferric phosphate is also reduced to 0.976. This proves that the batchwise addition of the phosphorus source solution and the oxidant solution is also the key to improving the iron-phosphorus ratio span and the average iron-phosphorus ratio of the anhydrous ferric phosphate.
[0311] (2) Related parameters of anhydrous ferric phosphate:
[0312] Depend on Figure 2 It can be seen that the anhydrous ferric phosphate prepared in Example 1 and Comparative Example 1 are consistent with the standard curve of FePO4. Figure 3 and Figure 4From the comparison, it can be seen that the particle size of the primary particles of anhydrous ferric phosphate prepared in Example 1 is slightly larger than that of the primary particles of anhydrous ferric phosphate prepared in Comparative Example 1.
[0313] As shown in Table 2, the average iron-phosphorus ratio of the anhydrous ferric phosphate prepared in Examples 1 to 18 is 0.978 to 0.985, and the average particle size of the primary particles is 270 nm to 330 nm, which has the characteristics of high average iron-phosphorus ratio and moderate average particle size of the primary particles; at the same time, its compaction density is 1.59 g / cm 3 ~1.62g / cm 3 , BET specific surface area is 9.72m 2 / g~11.95m 2 / g, with the characteristics of high compaction density and moderate BET specific surface area.
[0314] In Comparative Examples 1 and 2, no organic base solution was added, so that the average iron-phosphorus ratio of anhydrous ferric phosphate was reduced to 0.968, and the average particle size of the primary particles was reduced to 240nm~260nm, resulting in a decrease in the compaction density of the anhydrous ferric phosphate and an increase in the BET specific surface area. This shows that the organic base can effectively regulate the particle size of the primary particles of anhydrous ferric phosphate while improving the average iron-phosphorus ratio of the anhydrous ferric phosphate, thereby obtaining anhydrous ferric phosphate with a high average iron-phosphorus ratio, a moderate average particle size of the primary particles, a high compaction density, and a moderate BET specific surface area.
[0315] The preparation method of the anhydrous ferric phosphate in Comparative Example 3 is consistent with that in Example 1, and the measured average iron-to-phosphorus ratio, average particle size of primary particles, compacted density and BET specific surface area are comparable to those in Example 1.
[0316] In Comparative Example 4, the phosphorus source solution, oxidant solution and organic alkali solution are added to the ferrous solution at one time, so that the iron-phosphorus ratio of the anhydrous ferric phosphate is reduced to 0.976, and the average particle size of the primary particles is reduced to 245 nm, resulting in a decrease in the compacted density of the anhydrous ferric phosphate and an increase in the BET specific surface area. This shows that the batch addition of the phosphorus source solution and the oxidant solution also plays a dual role in regulating the average iron-phosphorus ratio of the anhydrous ferric phosphate and the average particle size of the primary particles.
[0317] (3) Relevant parameters of lithium iron phosphate positive electrode materials:
[0318] Depend on Figure 5 and Figure 6 From the comparison, it can be seen that the second particles of the lithium iron phosphate positive electrode material prepared in Example 1 have a high aspect ratio and present a slender columnar structure, while the second particles of the lithium iron phosphate positive electrode material prepared in Comparative Example 1 have a low aspect ratio and present a thick columnar structure or a granular structure.
[0319] As can be seen from Table 3, the lithium iron phosphate positive electrode materials obtained in Examples 1 to 18 include first particles and second particles, the particle size of the first particles is ≤200nm and the number accounts for 36.5% to 43.8%, the particle size of the second particles is ≥1μm and the number accounts for 1.03% to 4.74%, that is, the particle size of the first particles is small and the number accounts for a high proportion, and the particle size of the second particles is large and the number accounts for a low proportion. The average particle size of the primary particles of the lithium iron phosphate positive electrode materials obtained in Examples 1 to 18 is 270nm to 330nm, and the compaction density reaches 2.53g / cm 3 ~2.66g / cm 3 , BET specific surface area is 13.06m 2 / g~14.83m 2 / g, indicating that by regulating the particle size and quantity ratio of the first particles and the second particles, the average particle size of the primary particles of the lithium iron phosphate positive electrode material can be ensured to be small, and at the same time, the effect of large and small particle grading can be formed, thereby improving the compaction density of the lithium iron phosphate positive electrode material.
[0320] At the same time, in the lithium iron phosphate positive electrode materials prepared in Examples 1 to 18, the length of the second particles is 2.06μm to 8.96μm, the width is 0.37μm to 3.88μm, and the aspect ratio is 1.76 to 5.57, presenting a slender columnar structure, which can effectively inhibit the polarization effect of large single crystal particles and avoid a sharp decrease in the electrochemical performance of the battery using the lithium iron phosphate positive electrode material.
[0321] In the lithium iron phosphate positive electrode material prepared in Comparative Example 1, the number of first particles accounts for 40.25%, and the number of second particles accounts for 5.89%. Due to the high number of second particles, the average particle size of the primary particles increases to 340nm, and the compaction density decreases to 2.48g / cm 3 , indicating that the introduction of organic base can produce anhydrous iron phosphate with a large iron-phosphorus ratio span, a high average iron-phosphorus ratio, and a moderate average particle size of primary particles, thereby promoting a large number of anhydrous iron phosphates with a high iron-phosphorus ratio to generate a large number of lithium iron phosphate crystals with a small particle size, and a small number of anhydrous iron phosphates with a low iron-phosphorus ratio to generate a small number of lithium iron phosphate crystals with a large particle size, thereby ensuring that the average particle size of the primary particles of the lithium iron phosphate positive electrode material is smaller and the compaction density is higher. At the same time, the aspect ratio of the second particle of Comparative Example 1 is 1.30, showing a thick columnar structure, which is easy to cause the degradation of the electrochemical performance of the battery of the lithium iron phosphate positive electrode material, indicating that the anionic polymer has a good crystal form regulation effect, so that the second particle presents a columnar structure with a high aspect ratio, thereby improving the electrochemical performance of the battery using the lithium iron phosphate positive electrode material.
[0322] In the lithium iron phosphate positive electrode material prepared in Comparative Example 2, the number of first particles accounts for 43.2%, the number of second particles accounts for 0.94%, and the ratio of the number of the two reaches 45.96, resulting in the average particle size of the primary particles increasing to 335nm and the compaction density decreasing to 2.47g / cm 3 , which again shows that the introduction of organic base in the preparation process of anhydrous iron phosphate plays a key role in regulating the average particle size and compaction density of the primary particles of lithium iron phosphate positive electrode materials. At the same time, the aspect ratio of the second particles of comparative example 2 is 1.44, which is higher than the aspect ratio of the second particles of comparative example 1, proving that the introduction of anionic polymer plays a certain role in regulating the crystal form.
[0323] In the lithium iron phosphate positive electrode material prepared in comparative example 3, the aspect ratio of the second particles is 1.38, showing a thick columnar structure, which once again proves that the anionic polymer has a good crystal form regulation effect. At the same time, compared with Example 1, the number of second particles and the average particle size of primary particles in comparative example 3 are increased, but the compaction density is significantly reduced, indicating that the anionic polymer can also help regulate the particle size of the lithium iron phosphate positive electrode material, thereby increasing its compaction density.
[0324] In the lithium iron phosphate positive electrode material prepared in Comparative Example 4, the number of first particles accounts for 75.02%, and the number of second particles is reduced to 0.34%, which reduces the average particle size of the primary particles to 220nm and the compaction density to 2.35g / cm 3 This indicates that the batch addition of phosphorus source solution and oxidant solution can regulate the iron-phosphorus ratio span, average iron-phosphorus ratio and average particle size of primary particles of anhydrous iron phosphate, thereby affecting the particle size distribution and compaction density of lithium iron phosphate positive electrode materials.
[0325] (4) Relevant parameters of lithium iron phosphate positive electrode materials:
[0326] As shown in Table 4, the battery using the lithium iron phosphate positive electrode material prepared in Examples 1 to 18 has a 0.1C first charge specific capacity of 158.5mAh / g to 162.1mAh / g, a 0.1C first discharge specific capacity of 156.3mAh / g to 160.6mAh / g, a 0.1C first discharge efficiency of 97.28% to 99.69%, a 1C first charge specific capacity of 159.7mAh / g to 161.7mAh / g, a 1C first discharge specific capacity of 142.4mAh / g to 147.2mAh / g, and a 1C first discharge efficiency of 88.5% to 91.43%. Among them, the battery using the lithium iron phosphate positive electrode material prepared in Examples 1 to 18 has a 1C first discharge specific capacity that is higher than that of the battery using the lithium iron phosphate positive electrode material prepared in Comparative Examples 1 to 4, proving that the lithium iron phosphate positive electrode material prepared in Examples 1 to 18 has higher discharge performance.
[0327] In summary, the present application can effectively regulate the iron-phosphorus ratio of iron phosphate during the reaction process by introducing an organic base and adding a phosphorus source solution and an oxidant solution in batches, which is beneficial to improve the iron-phosphorus ratio span and average iron-phosphorus ratio of anhydrous iron phosphate, so that its average iron-phosphorus ratio is closer to the target iron-phosphorus ratio. On the other hand, the average particle size of the primary particles of anhydrous iron phosphate can be regulated, thereby obtaining an anhydrous iron phosphate with a large iron-phosphorus ratio span, a high average iron-phosphorus ratio, and a moderate average particle size of primary particles. Thus, using the anhydrous iron phosphate as a raw material, the number of the first particles and the second particles in the lithium iron phosphate positive electrode material can be effectively regulated, so that the average particle size of the primary particles of the lithium iron phosphate positive electrode material is smaller and the compaction density is higher. Further, in conjunction with the crystal form regulation effect of the anionic polymer, the aspect ratio of the second particle can be increased, so that it presents a slender columnar structure, so as to avoid the influence of the polarization of large single crystal particles on the discharge performance of the secondary battery, thereby improving the discharge performance of the secondary battery.
[0328] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A lithium iron phosphate positive electrode material, characterized in that: The average particle size of the primary particles of the lithium iron phosphate positive electrode material is 250nm to 330nm; The lithium iron phosphate positive electrode material includes first particles and second particles; The first particles meet the following requirements: particle size ≤ 200 nm, and the number accounts for 35% to 45%; The second particles meet the following requirements: particle size ≥ 1 μm, and the number accounts for 1% to 5%; The second particle has a columnar structure, and the ratio of the length to the width of the columnar structure is (1.7-6):
1.
2. The lithium iron phosphate positive electrode material according to claim 1, characterized in that: The expression of the lithium iron phosphate positive electrode material is LiFe 1-x M x PO4 / C; Among them, 0 <x≤0.1; The M element includes one or more of Mg, Ti, Mn, V, La, and Ce.
3. The lithium iron phosphate positive electrode material according to claim 2, characterized in that: The mass fraction of carbon element in the lithium iron phosphate positive electrode material is 1.20% to 1.28%.
4. The lithium iron phosphate positive electrode material according to any one of claims 1 to 3, characterized in that: The compaction density of the lithium iron phosphate positive electrode material is 2.53 g / cm 3 ~2.66g / cm 3 .
5. A method for preparing a lithium iron phosphate positive electrode material, characterized in that: The following steps are involved: preparing a precursor slurry containing anhydrous iron phosphate, a lithium source, a carbon source, a dopant, an anionic polymer and water; Dispersing, drying and sintering the precursor slurry to obtain the lithium iron phosphate positive electrode material; Wherein, the span of the iron-phosphorus ratio of the anhydrous ferric phosphate is ≥0.025, and the average iron-phosphorus ratio is 0.978-0.985; The average particle size of the primary particles of the anhydrous ferric phosphate is 270 nm to 330 nm.
6. The method for preparing the lithium iron phosphate positive electrode material according to claim 5, characterized in that: The preparation method of anhydrous ferric phosphate comprises the following steps: Mixing a ferrous solution, a phosphorus source solution, an oxidant solution and an organic base solution to obtain a first slurry; The first slurry is filtered, rinsed and pulped, and then the pH value is adjusted and the slurry is aged to obtain a second slurry; The second slurry is filtered, flashed and calcined to obtain the anhydrous ferric phosphate.
7. The method for preparing a lithium iron phosphate positive electrode material according to claim 6, characterized in that: One or more of the following conditions are met: (1) the molar ratio of the ferrous ions in the ferrous solution, the phosphate ions in the phosphorus source solution, the oxidant in the oxidant solution, and the organic base in the organic base solution is 1:(1.2-1.3):(2.3-2.8):(0.008-0.013); (2) The concentration of ferrous ions in the ferrous solution is 1.5 mol / L to 2 mol / L; (3) The pH value of the ferrous solution is 2.5 to 3.0; (4) The concentration of phosphate ions in the phosphorus source solution is 1 mol / L to 2 mol / L; (5) The pH value of the phosphorus source solution is 6.8 to 7.2; (6) the oxidant in the oxidant solution includes one or more of hydrogen peroxide, ammonium persulfate, sodium persulfate and sodium hypophosphite; (7) The concentration of the oxidant in the oxidant solution is 7.2 mol / L to 7.7 mol / L; (8) The organic base in the organic base solution includes one or more of triethanolamine and diethanol monoisopropanolamine; (9) The concentration of the organic base in the organic base solution is 0.010 mol / L to 0.015 mol / L.
8. The method for preparing a lithium iron phosphate positive electrode material according to claim 6, characterized in that: The step of mixing a ferrous solution, a phosphorus source solution, an oxidant solution and an organic base solution to obtain a first slurry comprises: The phosphorus source solution includes a first phosphorus source solution and a second phosphorus source solution, and the oxidant solution includes a first oxidant solution and a second oxidant solution; Mixing the ferrous solution, the first phosphorus source solution and the first oxidant solution to obtain a first mixed solution; Mixing the first mixed solution and the organic base solution to obtain a second mixed solution; The second phosphorus source solution and the second oxidant solution are sequentially added to the second mixed solution to obtain the first slurry.
9. The method for preparing a lithium iron phosphate positive electrode material according to claim 8, characterized in that: One or more of the following conditions are met: (1) The mass ratio of the first phosphorus source solution to the second phosphorus source solution is (65-80):(20-35); (2) The mass ratio of the first oxidant solution to the second oxidant solution is (70-85):(15-30); (3) the step of mixing the ferrous solution, the first phosphorus source solution and the first oxidant solution to obtain a first mixed solution, comprising: using the ferrous solution as a base solution, and simultaneously adding the first phosphorus source solution and the first oxidant solution to the base solution, the adding time being 20 min to 30 min, to obtain the first mixed solution; (4) the step of mixing the first mixed solution and the organic alkali solution to obtain a second mixed solution, comprising: adding the organic alkali solution to the first mixed solution and stirring for 20 min to 40 min to obtain the second mixed solution; (5) adding the second phosphorus source solution and the second oxidant solution to the second mixed solution in sequence to obtain the first slurry, comprising: adding the second phosphorus source solution to the second mixed solution, stirring for 2 min to 10 min, and dripping the second oxidant solution for 30 min to 50 min, and then stirring at 50° C. to 60° C. for 40 min to 80 min to obtain the first slurry; (6) The step of adjusting the pH value and subjecting the mixture to aging to obtain a second slurry comprises: adjusting the pH value to 1.0 to 1.7 using phosphoric acid, and heating the mixture to 90° C. to 95° C. for aging reaction until the pH value of the second slurry is 1.75 to 1.
85.
10. The method for preparing a lithium iron phosphate positive electrode material according to any one of claims 5 to 9, characterized in that: One or more of the following conditions are met: (1) The lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium sulfate, lithium nitrate, lithium phosphate and lithium chloride; (2) The dopant comprises one or more of magnesium oxide, titanium dioxide, manganese dioxide, vanadium pentoxide, ammonium metavanadate, lanthanum oxide and cerium oxide; (3) the molar ratio of the iron element in the anhydrous ferric phosphate, the lithium element in the lithium source and the doping element in the dopant is 1:(1.03-1.06):(0.005-0.007); (4) the carbon source comprises one or more of glucose, sucrose, fructose, ascorbic acid, polyethylene glycol, polyvinyl alcohol and starch; (5) The mass ratio of the carbon source to the anhydrous ferric phosphate is (13.6-15.2):100; (6) The anionic polymer comprises a polycarboxylic acid; (7) The number average molecular weight of the anionic polymer is 60,000 to 150,000; (8) The mass ratio of the anionic polymer to the anhydrous ferric phosphate is (1.5-2.4):
100.
11. The method for preparing a lithium iron phosphate positive electrode material according to any one of claims 5 to 9, characterized in that: The step of dispersing, drying and sintering the precursor slurry to obtain the lithium iron phosphate positive electrode material comprises: The precursor slurry is sand-milled and spray-dried at 200° C. to 240° C. to obtain a spray material; Under the protection of protective gas, the spray material is heated to 792° C. to 798° C. and kept warm for 8 h to 11 h to obtain the lithium iron phosphate positive electrode material.
12. A positive electrode sheet, characterized in that: The invention comprises the lithium iron phosphate positive electrode material according to any one of claims 1 to 4, or comprises the lithium iron phosphate positive electrode material prepared by the preparation method of the lithium iron phosphate positive electrode material according to any one of claims 5 to 11.
13. A secondary battery, characterized in that: Including the positive electrode sheet as described in claim 12.
Citation Information
Cited By
High-compaction-density lithium iron phosphate material, preparation method thereof and lithium ion battery
CN120622448A
A high-compaction-density lithium iron phosphate material, a preparation method thereof and a lithium ion battery
CN120622448B
Lithium iron phosphate material and preparation method thereof, positive pole piece and secondary battery
CN120757092A
Positive electrode material as well as preparation method and application thereof
CN120955127A